2013
DOI: 10.1371/journal.pone.0068675
|View full text |Cite
|
Sign up to set email alerts
|

Iron, Hepcidin and Inflammatory Status of Young Healthy Overweight and Obese Women in Australia

Abstract: Background and AimsEvidence suggests obesity-related inflammation alters iron metabolism potentially increasing the risk of iron deficiency. This cross-sectional study aimed to investigate iron, hepcidin and inflammatory status in young, healthy overweight and obese women.Methods114 young (18–25 years), healthy comorbidity-free women with a body mass index (BMI) ≥27.5 kg/m2 were recruited. Biochemical data were analysed using mean ± standard deviation or median (interquartile range) and multivariate modelling.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
22
3
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 23 publications
5
22
3
7
Order By: Relevance
“…Iron concentrations at steady-state were also affected by body size, as we found that iron absorption decreased when the body mass index increased. This result was observed in several studies revealing that iron concentration was lower for people with a high body mass index (36,37). A study performed on women aged between 18 to 25 years with a measured BMI ≥27.5 kg/ m 2 revealed the presence of inflammation with increasing body mass index.…”
Section: Discussionsupporting
confidence: 57%
“…Iron concentrations at steady-state were also affected by body size, as we found that iron absorption decreased when the body mass index increased. This result was observed in several studies revealing that iron concentration was lower for people with a high body mass index (36,37). A study performed on women aged between 18 to 25 years with a measured BMI ≥27.5 kg/ m 2 revealed the presence of inflammation with increasing body mass index.…”
Section: Discussionsupporting
confidence: 57%
“…This data was consistent with morbid obesity as described in others studies (2,18,19,36). A previous study has shown a correlation between hepcidin and ferritin values prior to surgery and a reduction of inflammation 6 months after surgery was associated with hepcidin and sTfR reductions (18).…”
Section: Discussionsupporting
confidence: 91%
“…In another study by Pinhas Hamiel et al [13], an association was found between BMI and serum iron. Also, Cheng et al [14] indicated the prevalence of anemia and iron deficiency as 10% and 17%, respectively. In their study, BMI could predict lower levels of serum iron, TIBC, and also CRP.…”
Section: Discussionmentioning
confidence: 99%